2007
DOI: 10.1111/j.1460-9568.2007.05419.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neuronal response to ischemia in retinas with genetic alterations of somatostatin receptor expression

Abstract: Ischemia is a primary cause of neuronal death in retinal diseases. The repertoire of expressed transmitter receptors would determine the neurons' responses to ischemic damage, and peptidergic receptors may be involved. With a new in vitro model of the ischemic mouse retina, we investigated whether an altered expression of somatostatin receptors could modulate retinal responses to ischemia. We used retinas of somatostatin receptor 1 (sst(1)) knock out (KO) mice, where sst(2) are over-expressed and over-function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
71
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 40 publications
11
71
2
1
Order By: Relevance
“…Some aspects of the developmental patterns of the somatostatinergic system in the retina, including early SST expression, the presence of transient expressing ganglion cells, and observations in SSTR KO mice, clearly indicate that this peptide has a variety of roles in retinal development [49,50,51,52,53]. Moreover, SSTR2 activation by SST or its analogues can protect retinal neurons against ischemia-induced damage [13], and studies in mice with genetic alterations of the somatostatinergic system have revealed that an increased presence of functional SSTR2 protects against retinal ischemia [54]. Therefore, SSTR2 analogues may be of therapeutic benefit in retinal diseases such as glaucoma or diabetic retinopathy, but may also protect from hearing loss due to HC degeneration and death.…”
Section: Discussionmentioning
confidence: 99%
“…Some aspects of the developmental patterns of the somatostatinergic system in the retina, including early SST expression, the presence of transient expressing ganglion cells, and observations in SSTR KO mice, clearly indicate that this peptide has a variety of roles in retinal development [49,50,51,52,53]. Moreover, SSTR2 activation by SST or its analogues can protect retinal neurons against ischemia-induced damage [13], and studies in mice with genetic alterations of the somatostatinergic system have revealed that an increased presence of functional SSTR2 protects against retinal ischemia [54]. Therefore, SSTR2 analogues may be of therapeutic benefit in retinal diseases such as glaucoma or diabetic retinopathy, but may also protect from hearing loss due to HC degeneration and death.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the excitotoxic glutamate is involved in retinal neurodegeneration induced by diabetes. Glutamate can be increased owing to ischemia or from dysfunction of glutamate metabolism and homeostasis, such as glutamate uptake, oxidation and turnover in the process of neurotransmission, involving both neuronal and Müller cells [130][131][132]. In our study, we found an increased level of branched-chain amino acids within diabetic retinas, which further augments the extracellular level of glutamate and, thereby, may be implicated in exacerbating the neurotoxicity [Ola MS et al, unpublished data].…”
mentioning
confidence: 53%
“…These observations have been replicated in an ex vivo model of the ischemic mouse retina, where the neuroprotective effects of SRIF have been shown to be mediated by the sst2 receptor. Indeed, these studies showed that an increased expression of functional sst2 receptors [40] or the use of SRIF or SRIF receptor agonists, such as the multireceptor ligand pasireotide and the sst2 receptor agonist octreotide [41], are effective in reducing the number of apoptotic neurons, the expression of apoptotic markers, such as caspase-3 mRNA, and the release of glutamate. In contrast, cell death is significantly increased after blocking sst2 receptors with the sst2 receptor antagonist cyanamide [41].…”
Section: Neuropeptides As Anti-ischemic Agentsmentioning
confidence: 99%
“…The experimental model that has been used to clarify for the first time the involvement of the sst2 receptor in the SRIF action against retinal ischemia [40] is a retina characterized by over-expression of functional sst2 receptors, caused by the genetic deletion of the sst1 receptor [28, 43-45]. It was expected that sst2 receptor agonist administration to these retinas resulted in increased protection from ischemic damage.…”
Section: Neuropeptides As Anti-ischemic Agentsmentioning
confidence: 99%